El docente y la comunidad de aprendizaje - Masapanta Pilliza, Pilar Jhiseth (2022)
Currently, education has undergone educational transformations where teachers are needed to be constantly updated in pedagogical areas, achieving the relationship between the teacher and the learning community with a harmonious work environment to play a good role. At the same time, it has been evidenced that teachers do not participate in collaborative activities, that is to say that individualism predominates, so collective participation oriented to the conformation of learning communities should be promoted in order to strengthen their professional competence. Therefore, the objective of this project is to involve the teacher in the learning community through collaborative activities to strengthen the teaching-learning process in the & quot; Juan Abel Echeverría " high school at Latacunga city in the academic period 2021-2022. The methodology used in the project is framed in qualitative research through the following stages: preparatory, fieldwork, analytical and informative. The method was inductive because the characteristics of teachers in learning communities were analyzed from the particular to the general. The technique used was the interview, with its instrument, the interview guide directed to authorities and teachers to obtain information about teamwork among teachers. The result was based on the reflection about the collaborative skills required by teachers to expand their knowledge based on collaboration and cooperation to feel confident to share their experience with other professionals, since their collective contribution is oriented to the improvement of their professional performance. When contrasting the information, it was established that teachers need to improve teamwork and be constantly updated to strengthen their professional competencies. Accordingly, this research contributes to the development of the collaboration of education professionals to respond about the changes required by teaching and learning today with a vision of continuous training to improve the educational and professional process.